Readiness Of Leaders, Teachers, Parents, And Students In Complying With Regulations In Inclusive Schools: A Study On Sports Education - Jasmine, Nadia; Ahmad, Masduki; Suryadi, Suryadi (Journal Coaching Education Sports, 2024)
Inclusive schools are a real implementation of the commitment to fair and equal education for all students, including those with special needs. One important aspect of inclusive schools is sports education, which is a medium for students' physical, social, and emotional development. This study aims to analyze the readiness of various parties—school leaders, teachers, parents, and students—in complying with the obligations of laws and regulations related to the implementation of inclusive schools, especially in the context of sports education. The method used is a literature review, by analyzing various sources of scientific literature, government policies, and relevant laws and regulations. The results of the study show that the readiness of each party varies greatly and is influenced by factors such as understanding the regulations, teacher competence in adapting inclusive sports teaching methods, parental support in accompanying children, and student acceptance of diversity in the learning environment. In addition, it was found that existing regulations still need strengthening in terms of socialization and technical implementation in the field. This study concludes that the success of inclusive schools, especially in sports education, is highly dependent on the synergy of all parties in understanding and carrying out their responsibilities in accordance with applicable regulations. Further recommendations include teacher training, outreach programs for parents, and the development of inclusive sports education modules.